Verification of the Indications of Honesty and Stability of the Scale of Envy (Benign , Malicious) Among Members of Society: A Psychometric Study - Yahya, Khatatbeh; Waed F, Mistarihi (Journal of Posthumanism, 2025)
The study aimed to verify the psychometric properties (honesty and stability) of the "benign" and "malicious" envy scale in the Arab environment, through the application of the Arabized version of the scale "(Lange & Crusius, 2015) on a sample of 282 members of the community. A cross-sectional quantum methodology was used to verify the validity of the scale. The results of the study indicated that The scale has an appropriate degree of honesty where The truthfulness of the content was verified by a panel of judges, the validity of the distinction by the difference between the highest and lowest quartile, and the validity of internal consistency through significant correlation coefficients between paragraphs and the overall score (0.642–0.789). Structural truthfulness was also verified through confirmatory factor analysis. (CFA) which showed a two-factor structure of the scale, and good statistical suitability (CFI = 0.95، RMSEA = 0.058). In terms of stability, the results showed Cronbach alpha coefficient (0.760 for benign envy, 0.782 for malignant envy) and omega coefficient (0.828, 0.867).) Respectively acceptable internal consistency. As the retest coefficient showed (t = 0.82) Stability of half fractionation (t = 0.78) Good time stability. The results indicate that the scale has the characteristics of Strong psychometric, suitable for use in the Arab environment to measure the dimensions of envy accurately and based on scientific foundations.